Characterisation of the modulation of immune response to polymer implants using established and novel methods - Suvannapruk, Waraporn (2023)
As understanding of host immune responses towards implanted biomaterials has grown, macrophages have been identified as critical predictors of inflammatory consequences following implantation. Depending on the phenotype they adopt in response to biomaterials in vivo, different macrophage phenotypes can either perpetuate chronic inflammation (via M1) or promote tissue healing (via M2). In the setting of tissue repair, a prompt shift in macrophage polarisation from a proinflammatory (M1 macrophages) to an anti-inflammatory (M2 macrophages) favours enhanced healing. In some cases, patients suffer adverse immune reactions to implanted devices leading to chronic inflammation, pain, and on occasion, implant failure. Therefore, it is beneficial to have an in-depth understanding of the metabolomics of different macrophage phenotypes, as this would help understand and improve the response of the human body to biomaterials.